Colored flexible shape-stabilized phase change energy storage material and preparation method thereof

By introducing polyethylene glycol and dye into the polymer framework, a new phase change energy storage material with adjustable phase change temperature, stable shape, good flexibility and bright colors was prepared, which solved the problems of single color and thermal flexibility of existing flexible phase change materials, and achieved widespread application in thermal management equipment and micro electronic equipment.

CN119569988AActive Publication Date: 2025-03-07DALIAN UNIV OF TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510029720.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-07
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing flexible phase change materials are single and not bright enough, and are mostly thermally flexible, limiting their application in thermal management equipment and micro electronic equipment.

Method used

By introducing polyethylene glycol and dye into the polymer framework, a new phase change energy storage material with adjustable phase change temperature, stable shape, good flexibility and bright colors were prepared. The material consists of organic polymer shaped phase transformation support material and mixed chain extender. The dye and small molecule chain extender are mixed in a certain proportion and are prepared by reaction and vacuum drying.

Benefits of technology

The adjustability of the phase transition temperature, the shape stability and flexibility of the material are achieved, and the bright colors can be displayed when the dye is added appropriately, which is suitable for thermal energy storage and release in special environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569988A_ABST
    Figure CN119569988A_ABST
Patent Text Reader

Abstract

The invention discloses a colored flexible shape-stabilized phase change energy storage material and a preparation method thereof, and belongs to the technical field of new materials. The preparation method comprises the following steps: reacting polyethylene glycol (PEG) with a bifunctional-group-containing compound to obtain a bifunctional-group-containing intermediate compound; the preparation method comprises the following steps: mixing dye molecules and a micromolecular chain extender according to a certain ratio to obtain a mixed chain extender, reacting according to the molar ratio of the mixed chain extender to the bifunctional intermediate compound of 1: 1, and introducing the dye molecules into a polymer skeleton to obtain the novel phase change energy storage material. The dye is mainly responsible for endowing the phase-change material with gorgeous color, and the micromolecule chain extender is mainly responsible for adjusting the flexibility of the phase-change material. The material is adjustable in phase change temperature, stable in shape, high in flexibility and good in toughness, and the material can still be endowed with bright color under the condition that the adding amount of dye is low. The material can be used for heat energy storage in a special environment. The material is simple in synthesis process, convenient to apply and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a colorful flexible shaped phase-change energy storage material and a preparation method thereof, and belongs to the technical field of new materials. Background Art

[0002] In recent years, energy shortage has been a major dilemma facing today's economic development. It is urgent to develop new energy storage technologies and improve energy utilization. Phase change energy storage materials (PCM) utilize the physical phase transition of materials to absorb or release a large amount of heat, thereby realizing the storage and utilization of thermal energy. It is one of the effective ways to improve the efficiency of thermal energy utilization. It has the advantages of high energy storage density, low price, and wide temperature range. It can effectively solve the problem of time and space mismatch between the supply and demand of thermal energy.

[0003] However, traditional phase change materials are highly rigid and have poor toughness. They are prone to brittle fracture when subjected to stress. Therefore, they are difficult to process and cannot be easily installed in devices with restricted space. In addition, it is difficult to achieve a tight fit with the device, which increases the contact thermal resistance and reduces the thermal management efficiency. Therefore, the preparation of flexible, shaped phase change materials has important application value.

[0004] However, flexible phase change materials also have certain problems. For example, most flexible phase change materials have intrinsic flexibility, are prone to leakage, have relatively single and dull colors, and have great limitations in practical applications.

[0005] In order to give phase change materials flexible properties, relevant researchers have prepared flexible phase change materials by physical embedding or chemical bonding. Sui Xiaofeng et al. applied for a patent for a flexible shaped composite phase change material. The treated cellulose sponge was immersed in a polyurethane solution, and a certain mass fraction of thermal conductive filler was added. After the immersion, the cellulose sponge was taken out and solidified in the mixed solution. After drying, a cellulose sponge / polyurethane composite material with a flexible and porous structure was obtained. The composite material has excellent mechanical properties, will not break when deformed below the melting point, and can still return to its original shape after the external force is removed, so that the material shows good flexibility and can withstand any reversible deformation above the melting point, which can effectively reduce the thermal resistance between it and the thermal management equipment, improve the convenience of actual installation, and expand its application in the field of thermal energy storage and management of microelectronic equipment. [Sui Xiaofeng, Wang Yating, Feng Xueling et al. A flexible shaped composite phase change material and its preparation method: CN110922944B[P]. 2019, 11, 05.]. However, most flexible phase change materials have a single color, not bright enough, and most of them are thermo-flexible, which limits their further application.

[0006] By introducing polyethylene glycol and dye into the polymer skeleton, the resulting phase change material has excellent shape stability, good phase change performance, intrinsic flexibility and bright colors. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a new type of organic flexible shaped phase change energy storage material with easily adjustable phase change temperature and bright colors. This material introduces polyethylene glycol and dye into the polymer skeleton to obtain a new type of phase change heat storage material with adjustable phase change temperature, stable shape, good flexibility and bright colors, which can be used for the storage and release of heat energy under special environments. This type of material has a simple synthesis process, is easy to use, and has broad application prospects.

[0008] A colorful flexible shaped phase-change energy storage material, wherein the colorful flexible shaped phase-change energy storage material is composed of the following components by mass percentage:

[0009] The material is composed of 95-99% by weight of an organic macromolecular shaped phase-change support material and 1-5% by weight of a mixed chain extender;

[0010] Preferably, the organic polymer shaped phase change support material is 97.8-98.3wt%; the mixed chain extender is 1.7-2.2%, and the mixed chain extender is obtained by mixing a dye and a small molecule chain extender, wherein the dye accounts for 0.6-46wt% and the small molecule chain extender is 54-99.4wt%.

[0011] The general structure of the organic polymer shaped phase change support material is as follows:

[0012]

[0013] Wherein, the structure of the linker A is , or ;

[0014] D= , , , , or ;

[0015] V 1 For Cl, F, NHCH 3 or NHC 4 H 9 ; V 2 H or CH 3 ; m = an integer from 100 to 10000; n = an integer from 10 to 1000.

[0016] The dye molecules and small molecule chain extenders are compounds containing dihydroxyl or diamino groups, which react with specific functional groups on the synthesized organic polymer shaping support material.

[0017] The colorful flexible shaped phase change energy storage material of the present invention is composited by an organic polymer shaped phase change support material and a mixed chain extender, wherein the organic polymer shaped phase change support material is a multi-block polymer phase change material with polyether as a soft segment and aromatic ring as a hard segment, and the mixed chain extender is obtained by mixing a small molecule chain extender and a dye in a certain proportion.

[0018] Preferably, the dye has a dihydroxyl or amino structure with similar reactivity. The following is a detailed description of the preferred dye structure:

[0019] For anthraquinone dyes, the chemical structural formula requirements are as follows:

[0020]

[0021] Among them, R 1 With R 2 The same structure, selected from OH, NH 2 , , , , Any of the following;

[0022] The azo dyes include heterocyclic azo dyes and non-heterocyclic azo dyes; wherein the general structural formula of the non-heterocyclic azo dyes is as follows:

[0023]

[0024] Among them, T 1 NO 2 , SCO 2 H 3 One of them, T 2 With T 3 They are H, Cl, Br, and NO respectively. 2 , CN, Y 1 ,Y 2 H, CH 3 、OCH 3 NHCOCH 3 、OCH 3 (OC 2 H 5 ) 、OC 7 H 5 (OCH 3 ), M 1 With M 2 CH 2 CH 2 OH, CH 2 Any one of OH;

[0025] The general structural formula of heterocyclic azo dyes is as follows:

[0026]

[0027] Among them, X is , , , , , , , , , , , , , , , Any one of L 1 , L 2 H, CH 3 、OCH 3 NHCOCH 3 、OCH 3 (OC 2 H 5 ) 、OC 7 H 5 (OCH 3 ), Q 1 ,Q 2 CH 2 CH 2 OH, CH 2 Any one of OH.

[0028] The chain extender is preferably a small molecule chain extender selected from the group consisting of N,N-dihydroxyethylaniline, triethylamine, propylene glycol, trimethylolethane, 1,4-butanediol, trimethylolpropane, dimethylolphenyl glycol, and 1,4-cyclohexanediol.

[0029] The preferred small molecule chain extender is one of N,N-dihydroxyethylaniline, triethylamine, propylene glycol, trimethylolethane, 1,4-butanediol, trimethylolpropane, dimethylethylenediol, and 1,4-cyclohexanediol.

[0030] A method for preparing a colorful flexible shaped phase-change energy storage material comprises the following process steps: dissolving an organic polymer shaped phase-change support material and a dye in a solvent in a certain proportion under stirring conditions; 2 The reaction was carried out at 80-120 °C for 4-12 h, the solvent was evaporated, and the product was obtained by vacuum drying.

[0031] In the above technical scheme, the solvent is preferably 1 to 3 of tetrahydrofuran, dioxane, acetone, chloroform, dichloromethane, carbon tetrachloride, carbon disulfide, DMF, DMSO, benzene, toluene, xylene, polyethylene glycol dimethyl ether, chlorobenzene, cyclohexane or n-hexane.

[0032] A method for preparing a colorful flexible shaped phase change energy storage material comprises the following steps:

[0033] (1) Polyethylene glycol with an average molecular weight of 2000-20000 was vacuum dried at 80 °C for 48 h.

[0034] (2) Dissolve polyethylene glycol and a bifunctional aromatic compound in a solvent at a molar ratio of 1:2, add an appropriate amount of catalyst, and 2 The above raw materials are added into a three-necked flask under a low temperature environment, and the reaction is stirred at 40-60 °C for 4-10 h to obtain a solution of an intermediate compound containing a bifunctional group.

[0035] Wherein, the compound containing a bifunctional group is a compound containing an epoxy, triazine or isocyanate structure; the mass ratio of the catalyst to the polyethylene glycol is 1:60-130; the mass ratio of the solvent to the polyethylene glycol is 7-14:1;

[0036] The solvent is one to three of tetrahydrofuran, dioxane, acetone, chloroform, dichloromethane, carbon tetrachloride, carbon disulfide, DMF, DMSO, benzene, toluene, xylene, polyethylene glycol dimethyl ether, chlorobenzene, cyclohexane or n-hexane.

[0037] (3) Add dye to the three-necked flask in a molar ratio of 1:1 between the dye and the intermediate compound obtained in step (2), and simultaneously add an equal amount of catalyst as in step 2, and react at 80-120°C for 4-12 hours to obtain an organic polymer shaped phase change support material.

[0038] The compound containing epoxy, triazine or isocyanate structure in the above step (2) is preferably a polyether structure compound containing an isocyanate group, wherein the isocyanate functional group is connected to the polyether through an ester bond.

[0039] The compound containing epoxy, triazine or isocyanate structure in the above step (2) is preferably a polyether structure compound containing a triazine group, wherein the triazine functional group is connected to the polyether through an ether bond.

[0040] The compound containing epoxy, triazine or isocyanate structure in the above step (2) is preferably a polyether structure compound containing epoxy group, wherein the epoxy functional group is connected to the polyether through an ether bond.

[0041] In the above step (2), the catalyst is preferably dibutyltin dilaurate.

[0042] The beneficial effects of the present invention are as follows: the material is reacted with a bifunctional compound through polyethylene glycol to obtain a bifunctional intermediate compound; the dye molecule and the small molecule chain extender are mixed in a certain proportion to obtain a mixed chain extender, and the mixed chain extender and the bifunctional intermediate compound are reacted in a molar ratio of 1:1, and then the solvent is evaporated by vacuum drying to finally obtain a new phase change energy storage material, wherein the organic polymer shaped phase change support material accounts for 97.8~98.3wt%; the mixed chain extender accounts for 1.7~2.2wt%, and the dye accounts for 0.6~46wt% in the mixed chain extender, that is, the dye accounts for 0.01~1wt% of the total weight of the material. The new color flexible phase change heat storage material has an adjustable phase change temperature, stable shape, good flexibility, and can still show bright colors when the amount of dye added is small, and can be used for the storage and release of heat energy under special environments. The material has a simple synthesis process, convenient application, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a digital photo of the purple phase change material prepared in Example 1-6.

[0044] Figure 2 This is the infrared spectrum of the purple phase change material obtained in Example 1.

[0045] Figure 3 This is the infrared spectrum of the blue phase change material obtained in Example 7.

[0046] Figure 4 This is the infrared spectrum of the orange phase change material obtained in Example 8.

[0047] Figure 5 This is a K / S value test chart of the purple phase change material prepared in Example 1.

[0048] Figure 6 This is a K / S value test chart of the blue phase change material prepared in Example 7.

[0049] Figure 7 This is a K / S value test chart of the orange phase change material prepared in Example 8.

[0050] Figure 8 This is the XRD curve of PEG10000 in Example 1.

[0051] Fig. 9 1, 2 and 3. The XRD curves of the color phase change materials prepared in Examples 1, 7 and 8 are shown in FIG.

[0052] Fig.10 This is the DSC performance test of the color phase change materials prepared in Examples 1, 7, and 8.

[0053] Fig.11 The tensile properties of the color phase change materials prepared in Examples 1, 7, and 8 were tested.

[0054] Fig.12 The shape-setting properties of the color phase change materials prepared in Examples 1, 7, and 8 were tested after being heated at 30°C, 60°C, and 80°C for 15 mins.

[0055] Fig.13 TG and DTG curves of the color phase change materials prepared in Examples 1, 7, and 8. DETAILED DESCRIPTION

[0056] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0057] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0058] (1) Polyethylene glycol with an average molecular weight of 2000-20000 was vacuum dried at 80 °C for 48 h.

[0059] (2) Polyethylene glycol and a compound containing a bifunctional group are dissolved in a solvent at a molar ratio of 1:2, and a catalyst dibutyltin dilaurate is added. The mass ratio of the catalyst to the polyethylene glycol is 1:60-130; the mass ratio of the solvent to the polyethylene glycol is 7-14:1; 2 Add the above raw materials into a three-necked flask under a certain environment, stir and react at 40-60 °C for 4-10 h to obtain a solution of an intermediate compound containing a bifunctional group. The intermediate compound containing a bifunctional group is an intermediate compound containing an epoxy group, an intermediate compound containing a triazine group, and an intermediate compound containing an isocyanate group. The solvent is 1-3 of tetrahydrofuran, dioxane, petroleum ether, acetone, butanone, chloroform, dichloromethane, carbon tetrachloride, carbon disulfide, DMF, DMSO, benzene, toluene, xylene, nitrobenzene, chlorobenzene, cyclohexane or n-hexane.

[0060] (3) Add dye to a three-necked flask in a molar ratio of 1:1 between dye and the intermediate compound containing a bifunctional group, add an equal amount of catalyst as in step (2), and react at 80-120° C. for 4-12 h to obtain a colorful flexible shape-fixed phase change material solution.

[0061] (4) Evaporating the solvent and vacuum drying to obtain a colorful, flexible, shaped phase change energy storage material.

[0062]

[0063] In the above table, in the intermediate compounds containing epoxy groups, PEG refers to polyethylene glycol, the number behind it is its molecular weight, and the epoxy functional group is connected to the polyether through an ether bond; in the intermediate compounds containing triazine groups, PEG refers to polyethylene glycol, the number behind it is its molecular weight, and the triazine functional group is connected to the polyether through an ether bond; in the intermediate compounds containing isocyanate groups, PEG refers to polyethylene glycol, the number behind it is its molecular weight, and the isocyanate functional group is connected to the polyether through an ester bond.

[0064] The above compounds 4# to 15# are prepared according to the method described in step (2): polyethylene glycol and a compound containing a bifunctional group (a compound containing epoxy, triazine or isocyanate structure) are dissolved in a solvent in a molar ratio of 1:2, and a catalyst is added. 2 The above raw materials are added into a three-necked flask with stirring in an environment, and reacted at 40°C for 8 hours to obtain a solution containing an intermediate compound; wherein the catalyst is dibutyltin dilaurate, and the mass ratio of dibutyltin dilaurate to polyethylene glycol is 1:100; and the solvent is toluene, and the mass ratio of dibutyltin dilaurate to polyethylene glycol is 10:1.

[0065] The compound containing a bifunctional group is a compound containing an epoxy, triazine or isocyanate structure. When preparing compounds 4# and 5#, the compound containing a bifunctional group is ethylene oxide; when preparing compounds 6# and 7#, the compound containing a bifunctional group is , when preparing compounds 8# and 9#, the compound containing bifunctional groups is ; When preparing compound 10#, the compound containing a bifunctional group is ; When preparing compound 11#, the compound containing a bifunctional group is ; When preparing compound 12#, the compound containing a bifunctional group is ; When preparing compound 13#, the compound containing a bifunctional group is ; When preparing compound 14#, the compound containing a bifunctional group is When preparing compound 6#, the compound containing a bifunctional group is ; When preparing compound 15#, the compound containing a bifunctional group is .

[0066] Example 1

[0067] (1) Polyethylene glycol with an average molecular weight of 10,000 was vacuum dried at 80 °C for 48 h.

[0068] (2) Polyethylene glycol and The mixture was dissolved in toluene at a molar ratio of 1:2, and dibutyltin dilaurate was added to the toluene. The mass ratio of dibutyltin dilaurate to polyethylene glycol was 1:100; the mass ratio of toluene to polyethylene glycol was 10:1; 2The above raw materials were added into a three-necked flask with stirring and reacted at 40 °C for 8 h to obtain a toluene solution containing a bifunctional intermediate compound; its structure is .

[0069] (3) 2.6 mg of dye 1# and 89.1 mg of small molecule chain extender 16# were mixed, with the dye accounting for 2.8 wt% and the small molecule chain extender accounting for 97.2 wt%. The mixed chain extender and 5.17 g of intermediate compound 9# containing a bifunctional group (in a molar ratio of about 1:1) were added to a three-necked flask for reaction. At the same time, an equal amount of catalyst as in step (2) was added. 2 After reacting at 80 °C in an environment for 10 h, a colorful flexible shape-fixed phase change energy storage material solution was obtained.

[0070] (4) Evaporating the solvent and vacuum drying at 80 °C for 10 to 24 h to obtain a colorful, flexible, and shape-fixed phase change energy storage material.

[0071] Example 2

[0072] The amount of dye added was adjusted so that its proportion in the total mass reached 1%, and the corresponding colorful flexible shape-fixed phase change energy storage material was obtained. The other conditions were consistent with those in Example 1.

[0073] Example 3

[0074] The amount of dye added was adjusted so that it accounted for 2% of the total mass to obtain the corresponding colorful flexible shaped phase change energy storage material. The other conditions were consistent with those in Example 1.

[0075] Example 4

[0076] The amount of dye added was adjusted so that it accounted for 3% of the total mass to obtain the corresponding colorful flexible shape-fixed phase change energy storage material. The other conditions were consistent with Example 1.

[0077] Example 5

[0078] The amount of dye added was adjusted so that its proportion in the total mass reached 0.01% to obtain the corresponding colorful flexible shape-fixed phase change energy storage material. The other conditions were consistent with those in Example 1.

[0079] Example 6

[0080] The amount of dye added was adjusted so that its proportion in the total mass reached 0.1% to obtain the corresponding colorful flexible shape-fixed phase change energy storage material. The other conditions were consistent with those in Example 1.

[0081] The appropriate amount of dye added was determined by performing a dye concentration gradient test. During the gradient test, the dye addition amounts were 0.01% (Example 5), 0.05% (Example 1), 0.1% (Example 6), 1% (Example 2), 2% (Example 3), and 3% (Example 4). The final results are as follows: Figure 1 As shown: When the dye addition amount is higher than 1%, as the dye addition amount increases, the color of the obtained material will gradually deepen and gradually deviate from the original color of the dye. When the dye addition amount is 0.05%, the effect is best, the coloring is uniform, and the original color of the dye can be displayed, and it has a bright color. Purple, orange, and blue phase change materials were prepared based on this concentration.

[0082] Example 7

[0083] Dye 2# was used to replace dye 1# for reaction to obtain a blue flexible shape-fixed phase change energy storage material. Other conditions were consistent with those in the above Example 1.

[0084] Example 8

[0085] Dye 3# was used to replace dye 1# for reaction to obtain an orange flexible shape-fixed phase change energy storage material. Other conditions were consistent with those in the above Example 1.

[0086] Figures 2 to 4 The infrared spectra of the phase change materials in Example 1, Example 7 and Example 8 are shown respectively. It can be seen that compared with the infrared spectra of the obtained colorful flexible shape-fixed phase change energy storage material, the original hydroxyl stretching vibration peak disappears, and the carbonyl stretching vibration peak (1716 cm -1 ) and the stretching vibration peak of amide II (1532 cm -1 ), which proves the formation of amide bonds, meaning that the dye is added to the polymer skeleton of the organic phase change support material by chemical bonding.

[0087] Figures 5 to 7 The K / S value tests of the phase change materials in Example 1, Example 7 and Example 8 are shown respectively. It can be seen that the prepared materials have bright colors, and their K / S values ​​are 9.8, 8.9, and 10.2 respectively, and the colors are bright.

[0088] Figure 8 is the XRD curve of PEG10000 in Example 1; Fig. 9 1 is the XRD curve of the color phase change material prepared in Examples 1, 7, and 8; from the XRD characterization of the material, it can be seen that the crystallization peak of the obtained color flexible shape-fixed phase change energy storage material is the same as the characteristic peak of polyethylene glycol, and has a crystalline characteristic.

[0089] Fig.10The DSC performance test of the colored phase change materials prepared in Examples 1, 7, and 8 shows that the phase change enthalpy of the obtained phase change material is relatively high, and the melting enthalpy and crystallization enthalpy are both around 98 J / g, which proves that the material has good phase change heat storage properties.

[0090] Fig.11 The tensile properties of the color phase change materials prepared in Examples 1, 7, and 8 were tested; the tensile properties results were: the tensile breaking strength was about 6.0 MPa, and the strain rate was about 550%, proving that the materials had excellent flexibility.

[0091] Fig.12 The color phase change materials prepared in Examples 1, 7, and 8 were tested for their shape-fixing properties after being heated at 30°C, 60°C, and 80°C for 15 mins. The figure shows that when the temperature is heated to 60°C, the polyethylene glycol begins to melt, while the obtained color flexible shape-fixing phase change energy storage material remains solid and does not flow even when the temperature rises to 80°C, indicating that the material has excellent shape-fixing phase change properties.

[0092] Fig.13 The TG and DTG curves of the color phase change materials prepared in Examples 1, 7, and 8 show that the color flexible phase change material has two decomposition steps. The first step is at about 230°C, which is the decomposition temperature of polyurethane, and the second step is above 400°C, which is the decomposition temperature of polyether. Therefore, the shaped phase change material prepared in the experiment has good thermal stability, and the decomposition temperature is much higher than its phase change temperature, which can ensure that it does not decompose during operation and has a wide application temperature range.

[0093] Examples 9-20

[0094] Compounds 4-8# and 10-15# are used to replace intermediate 9# in Example 1, and react with dye 1# to obtain the corresponding colorful flexible shape-fixed phase change energy storage material. Other conditions are consistent with Example 1.

[0095] Examples 21-32

[0096] Compounds 4-8# and 10-15# are used to replace intermediate 9# in Example 7 to react with dye 2# to obtain the corresponding colorful flexible shape-fixed phase change energy storage material. Other conditions are consistent with Example 7.

[0097] Examples 33-44

[0098] Compounds 4-8# and 10-15# are used to replace intermediate 9# in Example 8 to react with dye 3# to obtain the corresponding colorful flexible shape-fixed phase change energy storage material. Other conditions are consistent with Example 8.

[0099] Examples 45-52

[0100] Small molecule chain extender: N, N-dihydroxyethylaniline, triethylamine, propylene glycol, trimethylolethane, 1,4-butanediol, trimethylolpropane, dimethylbenzene glycol, 1,4-cyclohexanediol replaces the 16# small molecule chain extender in Example 1 and reacts with dye 1# to obtain the corresponding colorful flexible shape-fixed phase change energy storage material. Other conditions are consistent with Example 1.

Claims

1. A colorful, flexible, shaped phase-change energy storage material, characterized in that: The colorful flexible shaped phase change energy storage material is composed of 95-99% by weight of an organic polymer shaped phase change support material and 1-5% by weight of a mixed chain extender; wherein the mixed chain extender is obtained by mixing a small molecule chain extender and a dye molecule, and the mass percentage of the dye molecule in the mixed chain extender is 0.6-46wt%; The general structural formula of the organic polymer shaped phase change support material is as follows: ; Wherein, the structure of the linker A is , or ; D= , , , , or ; V1 is Cl, F, NHCH3 or NHC4H9; V2 is H or CH3; m = an integer from 100 to 10000; n = an integer from 10 to 1000.

2. A colorful, flexible, shaped phase-change energy storage material according to claim 1, characterized in that: The dye molecules include anthraquinone dyes or azo dyes The general structural formula of the anthraquinone dye is as follows: ; Wherein, R1 and R2 have the same structure and are selected from OH, NH2, , , , Any of the following: The azo dyes include heterocyclic azo dyes and non-heterocyclic azo dyes; wherein the general structural formula of the non-heterocyclic azo dyes is as follows: ; Wherein, T1 is one of NO2 and SCO2H3, T2 and T3 are any one of H, Cl, Br, NO2 and CN, Y1 and Y2 are any one of H, CH3, OCH3, NHCOCH3, OCH3(OC2H5) and OC7H5(OCH3), M1 and M2 are any one of CH2CH2OH and CH2OH; The general structural formula of heterocyclic azo dyes is as follows: ; Among them, X is , , , , , , , , , , , , , , , L1 and L2 are each any one of H, CH3, OCH3, NHCOCH3, OCH3(OC2H5), OC7H5(OCH3), Q1 and Q2 are each any one of CH2CH2OH, CH2OH.

3. The colorful, flexible, shaped phase-change energy storage material according to claim 1, characterized in that: The small molecule chain extender is N,N-dihydroxyethylaniline, triethylamine, propylene glycol, trimethylolethane, 1,4-butanediol, trimethylolpropane, dimethylolphenyl glycol or 1,4-cyclohexanediol.

4. The method for preparing the colorful flexible shaped phase change energy storage material according to any one of claims 1 to 3, characterized in that: The steps include: (1) vacuum drying polyethylene glycol with an average molecular weight of 2000 to 20000; (2) dissolving polyethylene glycol and a compound containing a bifunctional group in a solvent at a molar ratio of 1:2, and adding a catalyst, wherein the mass ratio of the catalyst to the polyethylene glycol is 1:60-130; stirring the reaction at 40-60°C in a N2 environment for 4-10 hours to obtain a solution of an intermediate compound containing a bifunctional group; the compound containing a bifunctional group is a compound containing an epoxy, triazine or isocyanate structure; and the mass ratio of the solvent to the polyethylene glycol is 7-14:1; (3) Physically mixing the dye and the small molecule chain extender in proportion to obtain a mixed chain extender, wherein the dye accounts for 0.6-46 wt %; reacting the mixed chain extender with the intermediate compound containing a bifunctional group, and simultaneously adding an equal amount of catalyst as in step (2), reacting at 80-120 ° C in a N2 environment for 4-12 h to obtain a colored flexible shape-fixed phase change energy storage material solution; (4) Evaporating the solvent and vacuum drying to obtain a colorful, flexible, shaped phase change energy storage material.

5. The method for preparing the colorful flexible shaped phase change energy storage material according to claim 4, characterized in that: The structure of the intermediate compound containing a bifunctional group is: 、 、 、 、 、 、 、 、 、 、 、 。 6. The method for preparing the colorful flexible shaped phase change energy storage material according to claim 4, characterized in that: The molar ratio of the mixed chain extender to the intermediate compound containing a bifunctional group is 1:1, wherein the molar amount of the mixed chain extender is the molar amount of the dihydroxyl group or the diamino group.

7. The method for preparing the colorful flexible shaped phase change energy storage material according to claim 4, characterized in that: The solvent is one to three of tetrahydrofuran, dioxane, acetone, chloroform, dichloromethane, carbon tetrachloride, carbon disulfide, DMF, DMSO, benzene, toluene, xylene, polyethylene glycol dimethyl ether, chlorobenzene, cyclohexane or n-hexane.

Citation Information

Patent Citations

  • A flexible, shape-stabilized composite phase change material and its preparation method

    CN110922944B

  • Photo-thermal conversion multiple-block macromolecule organic shape-stabilized phase change dye material

    CN102532945A

  • Organic phase stabilization, phase transition and energy storage material and preparation method thereof

    CN104910868A

  • Organic flame-retardant shape stable and energy store phase change material and preparation method thereof

    CN105820540A

  • Composite phase change material (PCM), method for manufacturing a composite PCM, and article of clothing including a composite PCM

    CN105980513A